Glycaemic measures for 8914 adult FreeStyle Libre users during routine care, segmented by age group and observed changes during the COVID‐19 pandemic. Issue 10 (17th July 2022) - Choudhary, Pratik; Kao, Kalvin; Dunn, Timothy C.; Brandner, Laura; Rayman, Gerry; Wilmot, Emma G.
Abstract: Aim: To evaluate the impact of the stay‐at‐home policy on different glucose metrics for time in range (%TIR 3.9‐10 mmol/L), time below range (%TBR < 3.9 mmol/L) and time above range (%TAR > 10 mmol/L) for UK adult FreeStyle Libre (FSL) users within four defined age groups and on observed changes during the coronavirus disease 2019 (COVID‐19) pandemic. Methods: Data were extracted from 8914 LibreView de‐identified user accounts for adult users aged 18 years or older with 5 or more days of sensor readings in each month from January to June 2020. Age‐group categories were based on self‐reported age on LibreView accounts (18‐25, 26‐49, 50‐64 and ≥65 years). Results: In January, prior to the COVID‐19 pandemic, the 65 years or older age group had the highest %TIR (57.9%), while the 18‐25 years age group had the lowest (51.2%) ( P < .001). Within each age group, TIR increased during the analysed months, by 1.7% (26‐49 years) to 3.1% (≥65 years) ( P < .001 in all cases). %TBR was significantly reduced only in the 26‐49 years age group, whereas %TAR was reduced by 1.5% (26‐49 years) to 3.0% (≥65 years) ( P < .001 in both cases). The proportion of adults achieving both of the more than 70% TIR and less than 4% TBR targets increased from 11.7% to 15.9% for those aged 65 years or older ( P < .001) and from 6.0% to 9.1% for those aged 18‐25 years ( P < .05). Mean daily glucose‐sensor scan rates were at least 12 per day and remained stable across the analysis period. Conclusions: Our data show the baseline glucose metrics for FSL users in the UK across different age groups under usual care. During lockdown in the UK, the proportion of adults achieving TIR consensus targets increased among FSL users.